Pengembangan Media Pembelajaran Progressive Web App Berbasis Environmental Learning untuk Meningkatkan Ecoliteracy Siswa - Hakiki, A.Riyan Rahman; Sumarmi, Sumarmi; Bachri, Syamsul; Mkumbachi, Ramadhani Lausi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2023)
Ecoliteracy as a practical solution to environmental problems. In the learning process at school, there is still no media that supports ecoliteracy learning. The research aims to develop a progressive web app learning media that is feasible and effective in improving students' ecoliteracy. This research uses the Research and Development method with the ADDIE model stages. The research subjects were 70 students of SMAN 1 Pamekasan consisting of 35 students of class XI F (experimental) and 35 students of class XI E (control). Determination of research subjects using simple random sampling technique. Data collection used interviews, questionnaires, and tests with qualitative and quantitative descriptive analysis techniques. The research produced a learning media progressive web app based on environmental learning that is feasible and effective. The implementation results show that the progressive web app based on environmental learning is an innovative solution to improve students' ecoliteracy.